Systematic review of islet cryopreservation. Issue 1 (2nd January 2018) - Kojayan, Greg G.; Alexander, Michael; Imagawa, David K.; Lakey, Jonathan R. T.
ABSTRACT: Pancreatic islet transplantation is being extensively researched as an alternative treatment for type 1 diabetic patients. This treatment is currently limited by temporal mismatch, between the availability of pancreas and isolated islets from deceased organ donor, and the recipient's need for freshly isolated islets. To solve this issue, cryopreservation of islets may offer the potential to bank islets for transplant on demand. Cryopreservation, however, introduces an overwhelmingly harsh environment to the ever-so-fragile islets. After exposure to the freezing and thawing, islets are usually either apoptotic, non-functional, or non-viable. Several studies have proposed various techniques that could lead to increased cell survival and function following a deep freeze. The purpose of this article is to critically review the techniques of islet cryopreservation, with the goal of highlighting optimization parameters that can lead to the most viable and functional islet upon recovery and/or transplant.